An environment for End-User Development of Web mashups. Issue 87 (March 2016) - Ghiani, Giuseppe; Paternò, Fabio; Spano, Lucio Davide; Pintori, Giuliano
Abstract: End-User Development aims to find novel ways that are suitable and intuitive for end users to create their own applications. We present a graphical environment in which users create new mashups by directly selecting interaction elements, content and functionalities from existing Web applications without requiring the intervention of expert developers. Then, users just need to exploit a copy–paste metaphor to indicate how to compose the selected interactive content and functionalities in the new mashup. The environment is enabled by a Web-based platform accessible from any browser, and is suitable for users without particular programming skills. We describe the architecture of our platform and how it works, including its intelligent support, show example applications, and report the results of first user studies. Highlights: An environment for creating Web mashups by direct manipulation of Web applications. Composition of novel applications from existing ones through a copy–paste metaphor. Web mashups solution that does not require pre-processing by expert developers. Mashup environment able to support modern dynamic Web applications.